Endlicheria lhotzkyi (Nees) Mez (Magnoliophyta: Laurales: Lauraceae): First record for the state of Mato Grosso do Sul, Brazil - Alves, Flávio Macedo; Frison, Sergianne [UNESP]; Lehn, Carlos Rodrigo (My University, 2012)
Endlicheria lhotzkyi is the first time recorded for the Brazilian state of Mato Grosso do Sul, collected in the municipal district of Sonora, north of the state. Taxonomic comments and an identification key of Endlicheria species from Mato Grosso do Sul is presented. © 2012 Check List and Authors.
Keywords: Endlicheria; Lauraceae; Laurales; Magnoliophyta